SIKAP SISWA MADRASAH DINIYAH TERHADAP PEMBATASAN PEMBELAJARAN AGAMA MASA PANDEMIK - Sarbini (GoAcademica Research dan Publishing, 2020)
This paper wants to know the impact of restrictions on religious education learning during the COVID-19 pandemic on the daily activities of madrasa students. The government's policy regarding the limitation of learning activities has the aim of breaking the chain of spread of Covid-19. This study uses a qualitative approach by utilizing data mining through in-depth interviews and focus group studies. The findings of this study include: First, madrasah students fully accept and comply with government policies regarding learning restrictions. Second, there is a new normal policy, which makes students' attitudes diverse, where some students have a less obedient attitude to the rules that are enforced. Third, adherence to learning restrictions is influenced by ideological beliefs about destiny. This study concludes that the attitudes of madrasah students towards learning restrictions have various forms, namely adaptive, persuasive, and antipathetic.